2001
DOI: 10.1002/1521-3951(200101)223:2<369::aid-pssb369>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Why Are the Conventionally-Assumed High-Pressure Crystal Structures of Ordinary Semiconductors Unstable?

Abstract: Recent high-pressure X-ray experiments show that, contrary to traditional expectations and numerous calculations, the NaCl structure is not present in covalent semiconductors, the diatomic b-Sn structure is absent in all compound semiconductors, and the CsCl structure is not seen in ionic semiconductors. We explain these systematic absences in terms of dynamical phonon instabilities of the NaCl, b-Sn, and CsCl crystal structures. Covalent materials in NaCl structures become dynamically unstable with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…74 Measurements of the phonon-dispersion relations under pressure performed recently 76 on PbTe have yielded a very small but negative value of ␥ TA for the X point, contrary to our calculations for ZnO. In contrast to calculations reported for GaP, 77 the rocksalt structure of ZnO exhibits a very small but positive Grüneisen parameter for the TA͑X͒ mode, as shown in Table VIII. This behavior may be related to the nonmetallic nature of the rocksalt modification of ZnO, which is deduced indirectly from the nonzero LO-TO splitting at the ⌫ point and has been recently observed in measurements of the optical absorption, and also obtained in ab initio calculations.…”
Section: Zinc Blende and Rocksaltcontrasting
confidence: 96%
See 1 more Smart Citation
“…74 Measurements of the phonon-dispersion relations under pressure performed recently 76 on PbTe have yielded a very small but negative value of ␥ TA for the X point, contrary to our calculations for ZnO. In contrast to calculations reported for GaP, 77 the rocksalt structure of ZnO exhibits a very small but positive Grüneisen parameter for the TA͑X͒ mode, as shown in Table VIII. This behavior may be related to the nonmetallic nature of the rocksalt modification of ZnO, which is deduced indirectly from the nonzero LO-TO splitting at the ⌫ point and has been recently observed in measurements of the optical absorption, and also obtained in ab initio calculations.…”
Section: Zinc Blende and Rocksaltcontrasting
confidence: 96%
“…78 GaP seems to be metallic in the rocksalt structure. 77 According to Table IV, the calculated values of ‫ץ‬Z*/‫ץ‬p are rather similar for the three ZnO modifications. This derivative can be related to the derivative of an effective charge with respect to the bond length.…”
Section: Zinc Blende and Rocksaltmentioning
confidence: 71%
“…36 We have investigated phonon modes at ⌫ point with a force-constant matrix diagonalization method, implemented in VASP, using the MS2 structure with a convenient hexagonal unit cell. MS2-LiB has two weakly interacting boron layers per unit cell which leads to an effective double degeneracy of the known phonon modes at ⌫ in the AlB 2 -type compounds.…”
Section: -2mentioning
confidence: 99%
“…Ab initio studies have shown that existence of energetically favorable phases could be barred by dynamical instabilities [36]. We have investigated phonon modes at Γ-point with a force-constant matrix diagonalization method, implemented in VASP, using the MS2 structure with a convenient rhombohedral unit cell.…”
mentioning
confidence: 99%
“…e.g. Dmitriev et al, 1988;Christy, 1993;O'Keeffe & Hyde, 1996;Zunger et al, 2001). Even phase transitions usually termed`reconstructive' may be regarded in an analogous way if the intermediate structure can be obtained by a step-by-step symmetry reduction leading to a sequence of subgroups of the space groups of both phases.…”
Section: Introductionmentioning
confidence: 99%